1998
DOI: 10.1292/jvms.60.291
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody against Dolphin Lymphocytes(6E9) which Recognizes Bovine MHC Class II Antigens.

Abstract: ABSTRACT. A monoclonal antibody, 6E9 established from mice injected with dolphin peripheral blood lymphocytes (PBLs) was characterized. In addition to its reactivity against 89.4% of dolphin PBLs, 6E9 reacted with 33.1% of bovine PBLs of which 22% were CD5 + , 11.1% were CD5 . 6E9 recognized a 34 kD protein on the surface of dolphin and bovine PBLs. Analysis of the protein's Nterminal amino acid sequence indicated that 6E9 recognizes bovine major histocompatibility complex (MHC) class II antigens. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Studies requiring the use of antibodies in marine mammals are challenging given the paucity of reagents available, and the lack of commercially available marine mammal specific antibodies. In addition to a small number of antibodies developed against marine mammal leukocyte subset markers (2329), several studies reported the use of cross-reactive monoclonal antibodies to label leukocyte subsets in marine mammals (3038). This study used blood samples from original target species or species with documented cross reactivity as positive control, to assure quality control in documenting lack of cross-reactivity with dolphin cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies requiring the use of antibodies in marine mammals are challenging given the paucity of reagents available, and the lack of commercially available marine mammal specific antibodies. In addition to a small number of antibodies developed against marine mammal leukocyte subset markers (2329), several studies reported the use of cross-reactive monoclonal antibodies to label leukocyte subsets in marine mammals (3038). This study used blood samples from original target species or species with documented cross reactivity as positive control, to assure quality control in documenting lack of cross-reactivity with dolphin cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caso BP 31. Hematoxilina e eosina, 200× (ROMANO et al, 1992;DE GUISE et al, 1997;SHIRAI et al, 1998).…”
Section: Padronização Das Reações Imuno-histoquímicasunclassified